Transformational Leadership Practices among Academic Administrators at a Public University in Malaysia - Samsudin, Norsamsinar; Abd. Razak, Ahmad Zainal Abidin; Abdul Jalil, Norasibah; Ab. Wahid, Hariyaty; Yaakub, Kamarul Bahari (International Business Education Journal, 2017)
This study aimed to investigate the practice of transformational leadership among academic administrators of a faculty at one of the public universities in Malaysia. Further, this study measured the level of leadership outcomes namely extra effort, effectiveness, and satisfaction. This study used all its population in the faculty, which consists of 71 full-time academicians. The MLQ 5X-Short was utilized as an instrument used to obtain the data. Academicians perceived their academic administrators’ leadership style as transformational (M = 2.42, SD = .55). The most practiced leadership style was inspirational motivation (M=2.72, SD = .60), followed by idealized influence (behavior) (M = 2.60, SD = .63) and idealized influence (attributed) (M = 2.42, SD = .64). The least frequent types of leadership styles were individual consideration (M=2.05, SD = .65), and intellectual stimulation (M = 2.32, SD = .71). However, the findings of this study revealed that the mean scores of the academicians at the university were below the mean scores of the normative sample for all transformational subscales. The result described that academic administrators displayed transformational leadership styles less than the normative sample. The study also discovered that the mean scores of the academicians were below the mean scores of the normative sample for all the leadership outcomes factors: extra effort, effectiveness, and satisfaction.